2003
DOI: 10.1002/aoc.476
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tributyltin(IV) chloride on fertilization of Styela plicata (Ascidiacea: Tunicata): II. Scanning and transmission electron microscopy studies

Abstract: The morphological aspects of Styela plicata fertilization after treatment with tributyltin(IV) chloride are described by means of scanning and transmission electron microscopy investigations. Alterations have been shown both on female and male gametes; spermatozoa, all the egg envelopes and the mitochondria of the egg cortical cytoplasm are modified in relation to incubation time. As a consequence, the damage to gametes blocks sperm-egg interaction and fertilization does not occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 14 publications
(16 reference statements)
1
8
0
Order By: Relevance
“…Data from literature indicated that TBT derivatives inhibited the egg-sperm recognition during the ascidian fertilization [60], and altered, immediately after the entry of spermatozoon into the cortex of egg, the normal fertilization cytoplasmic movements which are strictly connected to plasma membrane. TBT derivatives altered, also, the intracellular calcium homeostasis through inhibition of the membrane Ca 2+ -ATPase which activated several processes causing, at first, microfilaments and microtubules disassembly [61] or chromosomal disorders [62], alteration of cytoplasmic organelles and cell metabolism [10,60,63].…”
Section: Discussionmentioning
confidence: 99%
“…Data from literature indicated that TBT derivatives inhibited the egg-sperm recognition during the ascidian fertilization [60], and altered, immediately after the entry of spermatozoon into the cortex of egg, the normal fertilization cytoplasmic movements which are strictly connected to plasma membrane. TBT derivatives altered, also, the intracellular calcium homeostasis through inhibition of the membrane Ca 2+ -ATPase which activated several processes causing, at first, microfilaments and microtubules disassembly [61] or chromosomal disorders [62], alteration of cytoplasmic organelles and cell metabolism [10,60,63].…”
Section: Discussionmentioning
confidence: 99%
“…Mansueto et al 35 and Villa et al 36 Even if the 10 −5 M solution could be higher than those of the environmental antifouling coating found in the aqueous environment, many researchers have shown that the toxic effect on many processes of different species are dose and time dependent: 24,25,32 -36 the permanence of gametes, embryos and larvae in polluted environments varies in different species and consequently their integrity could be compromised in relation to the incubation time. In addition, it is known that the sediments accumulate organotin compounds and these can be remobilized and resuspended.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Fertilization, embryonic development and larval metamorphosis are seriously affected in tunicates. 9,10 In this way TBT, as with many other pollutants, can produce a reduction not only in their populations, but also in other species of marine biota. Immunotoxic effects of TBT have been reported in molluscs 11 and in tunicates.…”
Section: Speciation Analysis and Environmentmentioning
confidence: 99%